Impact of employee wellbeing on psychological empowerment: mediating role of happiness. (2017) - Pradhan, Rabindra Kumar; Hati, Lopamudra; Kumar, Updesh
The present study was carried out to examine the influence of employee wellbeing on psychological empowerment (i.e., meaning, competence, self-determination and impact). Efforts have been made to investigate the mediating role of happiness in relationship between employees' wellbeing and empowerment. A set of standard questionnaires on psychological empowerment, wellbeing and happiness was used for data collection. Data were collected on 96 executives randomly selected from Indian service sector. Multivariate statistics were used for analysis of the data. The results of the study revealed that employee wellbeing was positively associated with employee empowerment. Happiness was found to be a significant mediator between employee wellbeing and empowerment. Implications of the study were discussed in the context of Indian service industry for possible organisational development interventions to enhance employee wellbeing for greater empowerment.